Dataset: Indentation mechanical properties of chemically strengthened TiO2 doped soda lime silicate glass - Karlsson, Stefan (RISE Research Institutes of Sweden, 2022)
Titanium oxide has been added to the conventional soda lime silicate composition that is the most used glass in different applications. Surface mechanical properties through indentation using both nano- and micro-indenter has been studied both before and after chemical strengthening of the different glass samples.

Titanoxid har tillsatts till den konventionella soda kalk silikat sammansättningen som utgör det mest använda glaset i olika applikationer. Ytmekaniska egenskaper genom indentering med både nano- och mikroindenter har studerats både före och efter kemisk härdning av de olika glasproven.
Dataset: Ytmekaniska egenskaper för kemiskt härdade TiO2 dopade soda kalk silikat glas
Keywords: hardness; hårdhet; tempering (metalwork); härdning; physical properties; fysikaliska egenskaper; glass; glas; indentation; indentering; mechanical properties; mekaniska egenskaper; SCIENCE AND TECHNOLOGY; VETENSKAP OCH TEKNOLOGI; Materials Chemistry; Materialkemi; Materials Engineering; Materialteknik